Are Interracial Marriages an Indicator of Integration in the American Society? - Ahlem Hamzaoui (The Journal of Studies in Language, Culture and Society, 2018)
The paper aims to assess interracial marriage in the USA with a focus on the new generations. It discusses segregated laws that were enacted to prevent minorities from intermarrying whites to preserve white purity and supremacy through anti-miscegenation laws. The landmark Supreme Court case, Loving vs. Virginia (1967) is regarded as a turning point that led to the repeal of anti-miscegenation laws in the USA. A study was done to determine intermarriage of minority groups in the US and its leading forces, depending on rates and proportions of intermarriage. In this regard, it closely measured the degree of influence of new immigrant waves on intermarriage in the US. Besides the thorough examination of challenges that faced interracial communities, the paper was inclined to weigh the impact of interracial marriage on the integration of biracial children in the mainstream society and their racial identification.